Accounting for the UK Productivity Puzzle: A Decomposition and Predictions. (20th December 2016) - Goodridge, Peter; Haskel, Jonathan; Wallis, Gavin
Abstract : This paper revisits the UK productivity puzzle using new data on outputs and inputs and clarifying the role of output mismeasurement, input growth and industry effects. Our data indicate an implied labour productivity gap of 13 percentage points in 2011 relative to the productivity level on pre‐recession trends. We find that: (a) the labour productivity puzzle is a TFP puzzle, since it is not explained by the contributions of labour or capital services; (b) the reallocation of labour between industries deepens rather than explains the puzzle (i.e. there has been a reallocation of hours away from low‐productivity industries and toward high productivity industries); (c) capitalization of R&D does not explain the productivity puzzle; (d) assuming increased scrapping rates since the recession, a 25% (50%) increase in depreciation rates post‐2009 can potentially explain 15% (31%) of the productivity puzzle; (e) industry data show that 35% of the TFP puzzle can be explained by weak TFP growth in the oil & gas and finance sectors; and (f) cyclical effects via factor utilization could potentially explain 17% of the productivity puzzle. Continued weakness in finance would suggest a future lowering of TFP growth to around 0.8% p.a. from a baseline of 0.9% p.a.